2007
DOI: 10.1002/cbic.200700244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bicyclic Alkene‐/Alkane‐Bridged Nisin Mimics by Ring‐Closing Metathesis and their Biochemical Evaluation as Lipid II Binders: toward the Design of Potential Novel Antibiotics

Abstract: This report describes the design, synthesis, and biochemical evaluation of alkene‐ and alkane‐bridged AB(C)‐ring mimics of the lantibiotic nisin. Nisin belongs to a class of natural antimicrobial peptides, and has a unique mode of action: its AB(C)‐ring system binds to the pyrophosphate moiety of lipid II. This mode of action was the rationale for the design of smaller nisin‐derived peptides to obtain novel potential antibiotics. As a conformational constraint the thioether bridge was mimicked by an alkene‐ or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 88 publications
1
33
0
1
Order By: Relevance
“…To consider the role of lipid II as molecular target and its impact on binding intensity, 0.1 mol% lipid II was added to the matrix lipids. In accordance to other peptide/model membrane studies [27][28][29][30][31][32][33] and to avoid non-specific binding of the cationic antimicrobial peptides to the membrane surface, DOPC was initially selected as membrane lipid. As depicted in Fig 2A, [34,35], the gallidermin structure ( Fig.…”
Section: Kinetics Of Peptide Binding To Model Membranesmentioning
confidence: 99%
“…To consider the role of lipid II as molecular target and its impact on binding intensity, 0.1 mol% lipid II was added to the matrix lipids. In accordance to other peptide/model membrane studies [27][28][29][30][31][32][33] and to avoid non-specific binding of the cationic antimicrobial peptides to the membrane surface, DOPC was initially selected as membrane lipid. As depicted in Fig 2A, [34,35], the gallidermin structure ( Fig.…”
Section: Kinetics Of Peptide Binding To Model Membranesmentioning
confidence: 99%
“…4 macrocycle in a ratio of 2:1 after 16 h of refluxing in CH 2 Cl 2 [110,111]. Dicarba AB-and ABC-ring mimics of nisin were able to recognize its natural substrate lipid II, although with a tenfold reduced affinity compared to its native counterpart [114,115], while the DE-ring mimics were found to be devoid of membrane permeabilizing interactions [112,116].…”
Section: Synthesis Of Cyclic Peptides and Peptidomimetics By Metathesmentioning
confidence: 99%
“…4B, Ghalit et al reported that the conformational constraint of a thioether-part, -S-, is a similar to that of alkene or alkane. 40) In the present study, the pS-alkyl phenols and TDP can be regarded as positive compounds in terms of the estrogenic activity from the findings based on two bioassays. As a plausible reason for this positive activity, it should be noted that bioisosteric replacement between TDP and 4,4 -dihydroxystilbene (DHS) is valid, as shown in Fig.…”
Section: An Explanation Of Binding Ability On the Basis Of Bioisosterismmentioning
confidence: 85%